Analisis Pengaruh Financial Literacy, Future Orientation, Usia dan Gender terhadap Perencanaan Dana Pensiun PNS di Kota Surabaya - Kurnia Dwi Sandra; Achmad Kautsar (Jurnal Ilmu Manajemen, 2021)
Retirement planning is an important thing that should be a concern and implemented by every working people to achieve their happiness in retirement years, especially in countries like Indonesia, which experience a significant increase in the number of elderly each year. Focus on civil servants who are guaranteed pension funds from the government, each year, the number of workers who enter retirement age. This research aims to determine the effect of financial literacy, future orientation, age, and gender on retirement planning. The research sample is 110 respondents who are civil servants in Surabaya”collecting data by online questionnaires. The data analysis technique uses multiple linear regression by SPSS. This research results in financial literacy and future orientation positively affecting retirement planning. In contrast, the variables age and gender did not affect retirement planning.